PENGARUH BIAYA PRODUKSI, BIAYA OPERASIONAL, DAN VOLUME PENJUALAN TERHADAP LABA BERSIH PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2024 - Happy Noviyanti; Hadi Samanto; Muhammad Hasan Ma’ruf (CV. Denasya Smart Publisher, 2025)
This research aims to determine the effect of production costs, operational costs, and sales volume on the net profit of manufacturing companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange from 2021-2024. The objects studied in this research are manufacturing companies in the miscellaneous industry sector listed on the IDX from 2021-2024, totaling 48 companies. This type of research is quantitative. The research sample was selected using purposive sampling techniques, resulting in a sample of 16 companies. This research uses secondary data obtained from the Indonesian Stock Exchange (IDX). The data analysis techniques used include descriptive statistical tests, classical assumption tests, and hypothesis testing, which consist of multiple linear regression analysis, model feasibility test (F test), partial significance test (t test), and the coefficient of determination test. The results of this study indicate that production costs and operational costs have a significant negative effect on net profit, while sales volume has a significant positive effect on net profit.